What is the most sensitive test to identify fatigue through the analysis of neuromuscular status in male elite futsal players? - Moreno-Villanueva, A.; Rico-González, M.; Gómez-Carmona, C. D.; Gómez-Ruano, M. Á.; Silva, N.; Pino-Ortega, J. (Sensors, 2022)
The present study aimed to determine which of the neuromuscular status (NMS) monitoring tests (1: Counter-movement jump, CMJ; 2: back squat with additional load) is the most sensitive and effective for evaluating the state of fatigue in futsal players during the preseason. Seventeen professional futsal players were recruited for this study (age: 23.07 ± 6.76 years; height: 1.75 ± 0.06 m; body mass: 75.47 ± 7.47 kg; playing experience in elite: 5.38 ± 2.03 years). All of them were evaluated during the preseason phase in two tests (CMJ and back squat with additional load) before and after each training session (pre- vs. post-test). A jump platform was used to extract jump height during CMJ, while a linear position transducer was used to extract mean velocity (MV) and mean propulsive velocity (MPV) during the back squat exercise. Significant differences were obtained for intra-subject analysis for MV and MPV in loaded back squat exercise (p < 0.001), finding lower values during the post-test. In conclusion, the monitoring of NMS through the back squat provides greater sensitivity and objectivity in comparison with CMJ, due to a more direct neuromuscular extrapolation to the physical demands of futsal.